Gang rempit dan penyalahgunaan dadah: Pengaruhnya dari aspek psikososial dan institusi pendidikan - Don, Yahya; Daud, Yaakob; Kasa, Muhamad Dzahir; Sakdan, Mohd Fo'ad; Mustafa, Jamalluddin; Ahmad, Za'im (Agensi Antidadah Kebangsaan, 2009)
The purpose of this study was to investigate the influence of psychosocial environment and educational institution in Malaysia among ‘rempit group’ in drugs abuse. Specifically, this study is aim to identify of three aspects namely self-esteem, society and educational institution. This study also aims to identify whether there are significance difference between location, time, purpose and level of educations among rempit group. Two method of data collection was used namely quantitative and qualitative method.Coopersmith Self-Esteem Inventory (CSEI) (1967), peers, society and institution influence (Yahya Don, 1998) was used in this study, whereas observation and interview are used in qualitative method. A total of 2059 suspect of rempit group in Kedah, Pulau Pinang, Terengganu and Kuala Lumpur involved in this study. Interview involved rempit group, student’s counselor, police traffic, AADK officers, NGO’s and society members. Pearson correlation, MANOVA, t-test was used in analysis. Finding shows rempit group involved in drugs abuse are low of self esteem. A finding also shows there is significance correlation between educational institutions towards drugs abuse among rempit group. Overall, this study can explain the influence of psychosocial environment and educational institution towards drugs abused among rempit group. Lastly suggestion were given for minimize of drugs abuse among rempit group in Malaysia.